A mammalian capacitative calcium entry channel homologous to Drosophila TRP and TRPL - Philipp, Stephan; Cavalié, Adolfo; Freichel, Marc; Wissenbach, Ulrich; Zimmer, Stephanie; Trost, Claudia; Marquart, Andrea; Murakami, Manabu; Flockerzi, Veit (The EMBO journal, 1996)
Intracellular Ca2+ signalling evoked by Ca2+ mobilizing agonists, like angiotensin II in the adrenal gland, involves the activation of inositol(1,4,5)trisphosphate(InsP3)‐mediated Ca2+ release from internal stores followed by activation of a Ca2+ influx termed capacitative calcium entry. Here we report the amino acid sequence of a functional capacitative Ca2+ entry (CCE) channel that supports inward Ca2+ currents in the range of the cell resting potential. The expressed CCE channel opens upon depletion of Ca2+ stores by InsP3 or thapsigargin, suggesting that the newly identified channel supports the CCE coupled to InsP3 signalling.